Inhibition of pre-mRNA splicing by a synthetic Blom7α-interacting small RNA. - Marlies Löscher; Markus Schosserer; Eric Dausse; Kiseok Lee; Paul Ajuh; Regina Grillari-Voglauer; Angus I Lamond; Jean-Jacques Toulmé; Johannes Grillari; Johannes Grillari (PLoS ONE)
Originally the novel protein Blom7α was identified as novel pre-mRNA splicing factor that interacts with SNEV(Prp19/Pso4), an essential protein involved in extension of human endothelial cell life span, DNA damage repair, the ubiquitin-proteasome system, and pre-mRNA splicing. Blom7α belongs to the heteronuclear ribonucleoprotein K homology (KH) protein family, displaying 2 KH domains, a well conserved and widespread RNA-binding motif. In order to identify specific sequence binding motifs, we here used Systematic Evolution of Ligands by Exponential Enrichment (SELEX) with a synthetic RNA library. Besides sequence motifs like (U/A)(1-4) C(2-6) (U/A)(1-5), we identified an AC-rich RNA-aptamer that we termed AK48 (Aptamer KH-binding 48), binding to Blom7α with high affinity. Addition of AK48 to pre-mRNA splicing reactions in vitro inhibited the formation of mature spliced mRNA and led to a slight accumulation of the H complex of the spliceosome. These results suggest that the RNA binding activity of Blom7α might be required for pre-mRNA splicing catalysis. The inhibition of in-vitro splicing by the small RNA AK48 indicates the potential use of small RNA molecules in targeting the spliceosome complex as a novel target for drug development.